Synthesis of Nitride Zeolites in a Hot Isostatic Press. Issue 9 (23rd December 2020) - Wendl, Sebastian; Zipkat, Mirjam; Strobel, Philipp; Schmidt, Peter J.; Schnick, Wolfgang
Abstract: The recently introduced nitridophosphate synthesis in a hot isostatic press (HIP) enabled simple access to large‐scale product quantities starting from exclusively commercially available starting materials. Herein, we show that this method is suitable for the synthesis of highly condensed functional nitridophosphates, as well. Hence, the syntheses of the nitridophosphate zeolites Ba3 P5 N10 X ( X =Cl, Br) are presented as proof of concept for this innovative access. Furthermore, samples of unprecedented Sr3 P5 N10 X ( X =Cl, Br) were prepared and characterized to demonstrate the advantages of this synthetic approach over commonly used methods. Luminescence investigations on Eu 2+ ‐doped samples of AE 3 P5 N10 X ( AE =Sr, Ba; X =Cl, Br) were carried out and characteristics of observed emission bands are discussed. Abstract : Nitridophosphate zeolites AE 3 P5 N10 X ( AE =Sr, Ba; X =Cl, Br) were synthesized under medium‐pressure conditions (150 MPa N2, 1200 °C), extending the range of the degree of condensation for nitridophosphates accessible by hot isostatic pressing from κ =1/3 to 1/2. AE 3 P5 N10 X :Eu 2+ ( AE =Sr, Ba; X =Cl, Br) reveals natural‐white to deep‐red emission.